(untitled) (Scientific Journal of Research Studies in Future Management, 2023)
This research was conducted with the aim of investigating the factors affecting the resilience of human resources in the organization during the corona virus epidemic. The method of this descriptive research was exploratory and its community was all employees, experts and experts in the field of business management and human resources in the corona virus epidemic and... 385 people based on Cochran's formula using available sampling method. formed. In the resilience of human resources, the results of exploratory factor analysis showed that among the 36 existing indicators, 5 main factors can be identified. These factors were named based on the opinion of the experts and based on the content analysis of the concepts of personality traits, management patterns, organizational structure, organizational commitment and organizational justice. The total of the identified factors explained a total of 77% of the dispersion of human resource resilience in the coronavirus pandemic, and the structural equation model confirmed all the identified relationships.